2014 2nd International Conference on Technology, Informatics, Management, Engineering &Amp; Environment 2014
DOI: 10.1109/time-e.2014.7011602
|View full text |Cite
|
Sign up to set email alerts
|

A study on kerf and material removal rate in wire electricaldischarge machining of Ti-6Al-4V: multi-objectives optimization

Abstract: This paper presents an investigation on the effect and optimization of machining parameters on the kerf (cutting width) and material removal rate (MRR) of titanium alloy (TI-6AL-4V) using wire electrical discharge machining WEDM with a brass wire diameter of 0.5mm. The experimental studies were conducted under varyingpulse-off time, peak current, wire feed and wire tension. The settings of machining parameters were determined by using Taguchi experimental design method. The multiple performance characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…T off is most contributing factor (41.73%) on MRR followed by T on and current. Saedon et al [ 30 ] also reported T off as the most significant factor (58%) while investigating WEDM machining on Ti-6Al-4V alloy. The R 2 value of 98.29% indicates that 98.29% of the variation of MRR can be explained by the empirical model and only 1.71% of total variation cannot be described by the developed model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…T off is most contributing factor (41.73%) on MRR followed by T on and current. Saedon et al [ 30 ] also reported T off as the most significant factor (58%) while investigating WEDM machining on Ti-6Al-4V alloy. The R 2 value of 98.29% indicates that 98.29% of the variation of MRR can be explained by the empirical model and only 1.71% of total variation cannot be described by the developed model.…”
Section: Resultsmentioning
confidence: 99%
“…This further increases the MRR by a large amount. Saedon et al [ 30 ] attributed increasing MRR with increasing T on and current to the reduced dynamic shear strength of Ti alloy due to higher thermal influence in the machining region. The outcome of T off on MRR shows a decreasing trend with a rise in T off because of reduced spark ejection time and less MRR [ 9 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of the dependent variable to the factor is determined by the variance associated with the factor. Since the method of analysis of variance has been widely used in various fields, such as fitting the expression of material strength and material composition in the material field [25,26], this paper employs the analysis of variance method to quantify the influence of various parameters on the pullout factor of the anchor plate for c > 0 kPa and φ > 0 °.…”
Section: Analysis Of Variance On N Smentioning
confidence: 99%
“…It is a concern that the derivation of theoretical formula of the pullout factor expression is too difficult to be described in previous researches. However, the method of fitting the expression of material strength and material composition in the material field [25,26] shows that the data analysis methods can determine the effect of related factors and the form of expression when reliable data is available.…”
Section: Introductionmentioning
confidence: 99%